Enhancement of corn stover hydrolysis with rumen fluid pretreatment at different solid contents: Effect, structural changes and enzymes participation. (April 2017) - Li, Fan; Zhang, Panyue; Zhang, Guangming; Tang, Xiang; Wang, Siqi; Jin, Shuguang
Abstract: Different solid contents of corn stover were pretreated with rumen fluid to enhance its hydrolysis and acidification, with whole pretreatment time of 72 h. Results showed that rumen fluid pretreatment effectively enhanced the hydrolysis of corn stover. The concentration of soluble COD for 10% ( w/v ) corn stover was about 2–6.4 times and 1.5–2.5 times of that for 3% and 5% ( w/v ), respectively. The highest reducing sugar concentration for 10% ( w/v ) corn stover was about 20 folds and 5.7 folds of that for 3% and 5% ( w/v ) at 2 h, respectively. Higher solid content of corn stover produced more VFAs, however, VFAs accumulation happened during the 10% ( w/v ) corn stover pretreatment, leading to the higher VFAs concentration for 5% ( w/v ) corn stover than that for 10% ( w/v ) during the 16–36 h. After the pretreatment, the structure of corn stover changed, such as the increase of specific surface area and decrease of crystallinity. Due to the removal of hemicellulose, the relative amount of lignin increased in the treated solids illustrated by the FTIR spectra. The changes of enzymatic activities showed that the enzymes secreted by the rumen microorganisms were quickly adsorbed by the corn stover, participating in the hydrolysis, which resulted in the sharp decrease of enzymatic activities in the fluid at the first 4 h. Though the enzymatic activities increased a little during the pretreatment, they could not restore the original level. This might be caused by the pH decrease and VFAs accumulation. The practical application prospect of this study was also conducted. Graphical abstract: Highlights: Rumen fluid pretreatment of corn stover showed enhanced production of VFAs. Rumen fluid pretreatment is feasible for 10% ( w/v ) corn stover. There were structural changes of corn stover after rumen fluid pretreatment. Enzymes participated hydrolysis of corn stover.